- PELANGGARAN SYARAT ADMINISTRASI DALAM PROSES PENGGANTIAN ANTAR WAKTU (PAW) DEWAN PERWAKILAN RAKYAT DAERAH KOTA TANJUNG BALAI - Muhamad Azriel Hafidz; Ferry Edwar (Reformasi Hukum Trisakti, 2023)
The Tanjung Balai City Police made negligence in issuing a Police Record Certificate which led to MM  being appointed as a member of the Tanjung Balai City Legislatif, because the SKCK itself is an administrative requirement while MM  is a drug dealer. The main problem is what is the violation of administrative requirements in the Inter-Time Reimbursement process, MM , according to statutory regulations. This study uses a normative method, which is equipped with the results of interviews. The research results show that MM  was proven to have violated the administrative requirements stipulated in Law Number 7 of 2017 concerning General Elections Article 240 paragraph (1) letter h jo General Election Commission Regulation Number 20 of 2018 Concerning the Nomination of Members of the People's Legislative Assembly, Provincial Regional People's Representative Council, and Regional Council Regency/City Regional People's Representative Representatives Article 7 paragraph (1) letter i is proven by decision number 773/Pid.Sus/2021/PN Mdn